Entrepreneurship-Based Non-Formal Education Program Development Through Coaching Clinic - Widodo, Widodo; Atmaja , I Ketut; Siswanto , Heru; Firmansyah , Arif; Yusuf , Ali (Journal of Nonformal Education, 2024)
The Community Learning Center (CLC) as a Non Formal Education (NFE) unit has the principles of ’from’, ’by’ and ’for’ the community in management. CLC has an equality education Package program which is an alternative solution for affordable primary and secondary education services. Development of the NFE program at CLC based on entrepreneurship through coaching clinics with activities; delivery of material related to the NFE program and independence strategy, consulting on various problems faced by CLC, field visits to ensure the strategies chosen in developing the NFE program can be implemented properly, and building a shared commitment to developing the NFE program, so as to create self-reliance based CLC entrepreneurship. The objective of this research is to analyze the implementation of Package equality learning based on entrepreneurship in creating independence. This research uses descriptive qualitative, with data analisys; (1) data reduction through department-interviews, participant observation, documentation, (2) data display, (3) conclusions. As for checking the validity of the data to measure the degree of trust (credibility) with transferability and confirmability. The results of the study show changes in conducting entrepreneurship learning for Package students which are more contextual and emphasize hands-on practice. Entrepreneurship-based NFE program development carried out in CLC is carried out through 3 stages, namely (1) the stage of context analysis and identification of community learning needs in which there are problems and resources that can be used for learning. (2) The stage of managing entrepreneurship learning which includes planning, organizing, implementing, and supervising entrepreneurship learning programs. (3) The evaluation stage is carried out to find out the learning outcomes and processes. Learning outcomes through theory and performance exams during practical work, while process evaluation is carried out at each stage of implementing entrepreneurship learning. The conclusion is that the development of an entrepreneurship-based NFE program through a coaching clinic can provide changes in the management of culinary and barista entrepreneurship learning as a program advantage in CLC. The novelty of this research is learning equality education packages combined with vocational skills which accelerate students’ independence.